Low emission zones: Effects on alternative-fuel vehicle uptake and fleet CO2 emissions. (June 2021) - Peters, Jens F.; Burguillo, Mercedes; Arranz, José M.
Graphical abstract: Highlights: Assessment of low emission zone (LEZ) as potential decarbonisation instrument. Econometric approach based on vehicle registration and real life fuel consumption data. LEZ as effective measure for fostering alternative fuel vehicle uptake. Support of hybrid and gas-powered vehicles impedes reaching CO2 targets. LEZ ineffective for reducing fleet CO2 emissions; zero emission zone required. Abstract: This study analyses the effect of a representative low-emission zone (LEZ) in Madrid on shifting vehicle registrations towards alternative fuel technologies and its effectiveness for reducing vehicle fleet CO2 emissions. Vehicle registration data is combined with real life fuel consumption values on individual vehicle model level, and the impact of the LEZ is then determined via an econometric approach. The increase in alternative fuel vehicles (AFV) registration shares due to the LEZ is found to be significant but fosters rather fossil fuel powered AFV and plug-in hybrid electric vehicles (PHEV) than zero emission vehicles. This is reflected in the average CO2 emissions of newly registered vehicles, which do not decrease significantly. In consequence, while the LEZ is a suitable measure for stimulating the shift towards low emission vehicles, a true zero emission zone would be required for effectively fostering also the decarbonization of the vehicle fleet.